GLOBALLY-CONSTANT SPEED OF LIGHT C : A BONANZA IN PHYSICS - Rossler, Otto E. (European Scientific Journal, ESJ, 2013)
The historical twist that the universal constancy of the speed of light, c , got abandoned for more than a century is recalled. The proposed new situation – global constancy of c – is described in some detail. Its uplifting consequences include a new metrology and a new cosmology.